2016
DOI: 10.1638/2015-0236.1
|View full text |Cite
|
Sign up to set email alerts
|

GROSS ANATOMY AND SURGICAL APPROACH TO THE HUMERAL SHAFT IN GIANT ANTEATER (MYRMECOPHAGA TRIDACTYLA)

Abstract: Anteater forelimbs are distinguished morphologically from domestic animals, especially due to their unique movement and their natural habits. A knowledge of the pectoral limb anatomy and the proper surgical approach are fundamental to success in osteosynthesis and other surgeries. This study aimed to describe the muscles and neurovascular structures of the pectoral limb and the surgical approach to the humeral shaft of the giant anteater ( Myrmecophaga tridactyla ). Dissections of the forelimbs of seven cadave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In Myrmecophaga , the FDP has five heads: radial, ulnar, olecranon, humeral, and other heads originating from the TBMH tendon (Macalister, 1875a; Pouchet, 1867; Windle & Parsons, 1899), and it can connect the tendons to the digits I–IV (Macalister, 1875a; Pouchet, 1867) or II‐IV (Windle & Parsons, 1899). In two recent studies on Myrmecophaga , the TBMH was observed to be continuous with the FDP (García et al, 2019; Sesoko et al, 2016); however, the detailed description of these muscles was not provided. In Cyclopes didactylus , the FDPb and FDPls were absent in the FDP; therefore, the FDP in Cyclopes only has three common heads (humeral, radial, and ulnar) and connects tendons to digits II and III (Galton, 1869a; Humphry, 1869; Macalister, 1875a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Myrmecophaga , the FDP has five heads: radial, ulnar, olecranon, humeral, and other heads originating from the TBMH tendon (Macalister, 1875a; Pouchet, 1867; Windle & Parsons, 1899), and it can connect the tendons to the digits I–IV (Macalister, 1875a; Pouchet, 1867) or II‐IV (Windle & Parsons, 1899). In two recent studies on Myrmecophaga , the TBMH was observed to be continuous with the FDP (García et al, 2019; Sesoko et al, 2016); however, the detailed description of these muscles was not provided. In Cyclopes didactylus , the FDPb and FDPls were absent in the FDP; therefore, the FDP in Cyclopes only has three common heads (humeral, radial, and ulnar) and connects tendons to digits II and III (Galton, 1869a; Humphry, 1869; Macalister, 1875a).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that the FDPb in Tamandua was formed upon the fusion of the TBMH with the FDP based on an analysis of its origin from the humerus in Tamandua and Myrmecophaga (García et al, 2019; Macalister, 1875a; Sesoko et al, 2016; Taylor, 1978; Windle & Parsons, 1899), and the innervation pattern was not considered. In a study on the brachial plexus in T. tetradactyla , the authors mentioned that TBMH was innervated by the ulnar nerve (Cruz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It's almost straight structure differs from domestic animals, in which the humerus has a spiral shape due to the sulcus m. brachialis (KÖNIG & LIEBICH, 2021). The distal extremity of the humerus is flattened craniocauldally, as observed in the anteater, presenting developed epicondylus that offer great area for fixation of the powerful flexor and extensor muscles of the carpus and the fingers (SESOKO et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As for the musculature of the arm of B. variegatus, M. latissimus dorsi origin had its origin from the posterior half of the spinal processes of the thoracic vertebrae inserting medially in the proximal portion of the humerus, as described by NYAKATURA & FISCHER (2011) for the sloths Choloepus didactylus and Bradypus variegatus. Some fibers of the M. latissimus dorsi extend as a continuation to M. tensor fasciae antebrachii, which is inserted into the olecranon, similar to the giant anteater (SESOKO et al, 2016) The M. triceps brachii consisted of two heads, lateral and longum, which originated at the caudal end of the scapula (caput longum) or at the proximal end of the humerus (caput laterale) and were inserted into the Tuber olecrani. MILLER (1935) described three caputs for the genus Bradypus (laterale, longum and mediale), as well as for equine, bovine and swine (KÖNIG & LIEBICH, 2021).…”
Section: Discussionmentioning
confidence: 99%